2016
DOI: 10.1590/1809-4392201505883
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal parasites in two indigenous ethnic groups in northwestern Amazonia

Abstract: Approximately 90% of the population in the northwestern Amazonia is composed of indigenous people and their healthcare is still a challenge. The objective of this study was to determine the frequency of parasites in two indigenous ethnic groups (Baré and Baniwa) in northwestern Amazonia. Stool samples from 270 individuals (199 Baniwa and 71 Baré) were analyzed using Richie's method and the spontaneous sedimentation method. Statistical differences among the proportions of infected individuals based on gender, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
(47 reference statements)
1
4
0
1
Order By: Relevance
“…Entamoeba coli (41.9%) and Endolimax nana (37.2%), and the helminth Hymenolepis nana (23.3 %). These results are similar to those observed in other studies with indigenous populations from Paraná (Scolari et al, 2000;Novak et al, 2016;Moura et al, 2010) and from other locations (Anderson et al, 2014, Fontbonne et al, 2001, Oliveira et al, 2016, although the majority of them had a lower frequency of H. nana. Kato-Katz method was not used to assess the parasitic load of geohelminths, which would be a limiter for the assessment.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Entamoeba coli (41.9%) and Endolimax nana (37.2%), and the helminth Hymenolepis nana (23.3 %). These results are similar to those observed in other studies with indigenous populations from Paraná (Scolari et al, 2000;Novak et al, 2016;Moura et al, 2010) and from other locations (Anderson et al, 2014, Fontbonne et al, 2001, Oliveira et al, 2016, although the majority of them had a lower frequency of H. nana. Kato-Katz method was not used to assess the parasitic load of geohelminths, which would be a limiter for the assessment.…”
Section: Discussionsupporting
confidence: 92%
“…and G. duodenalis were more common in indigenous children, while A. lumbricoides and hookworms were more common in adults (Anderson et al, 2014). Intestinal protozoa may be non-pathogenic, but some species such as E. histolytica, G. duodenalis and Blastocystis hominis are responsible for cases of diarrhea, malabsorption and malnutrition (Oliveira et al, 2016). These enteroparasites can be transmitted by water, food or direct contact between people, and can contribute to impaired school performance and physical development of children (Fontbonne et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…From this perspective, it was observed that the epidemiological profile of those communities contributes to the spread of the disease due to unfavorable economic conditions and precarious basic sanitation present in some villages. [26][27] The causes of the presence of such diseases were inferred to be the imbalance of territorial invasions in the Legal Amazon and the insertion of life habits of non-indigenous people in urban and rural areas. 5,28 It was observed in this study that gender representativeness was illustrated by Brazilian indigenous women, by the power and participation of women in politics and in work in an indigenous community in the state of Mato Grosso do Sul.…”
Section: VImentioning
confidence: 99%
“…Na Amazônia, os povos indígenas experimentam uma trajetória histórica de subordinação e desvantagem socioeconômica, num cenário de iniquidades que são traduzidas em piores indicadores de saúde, como alta mortalidade infantil, elevadas prevalências de desnutrição infantil, maiores taxas de morbidade e mortalidade por doenças infecto-parasitárias 3,4,5,6,7,8,9 . Entretanto, embora as doenças transmissíveis permaneçam como as principais causas de morbimortalidade indígena, observa-se o crescimento dos agravos externos e doenças crônicas não transmissíveis, com destaque para obesidade, hipertensão arterial, diabetes e neoplasias, no contexto de transição epidemiológica vivenciado por esses povos nas últimas décadas 10,11,12,13 .…”
Section: Introductionunclassified